Natural Bio‐additive Chlorophyll Derivative Enables 17.30% Efficiency Organic Solar Cells - Duan, Shengnan; Sasaki, Shin‐ichi; Han, Deman; Zhang, Guangquan; Li, Dengfeng; Feng, Chunbao; Wang, Xiao‐Feng; Tamiaki, Hitoshi; Chung, Sein; Cho, Kilwon; Li, Gang; Lu, Shirong (Advanced functional materials, 2023)
Additive‐assisted donor and acceptor domain regulation is regarded as an effective strategy to further release the potential photovoltaic performance of the existing organic solar cells (OSCs). Meanwhile, it is also critical to find high‐efficient, stable, non‐toxic, and low‐cost biological materials as bio‐additives to replace the traditional toxic halogen‐based additives. In this study, bio‐additives derived from a natural chlorophyll pigment named as ZnChl and H 2 Chl are employed to optimize the morphology and molecular stack of the PM6:Y6 active layer. The eutectic molecular stack of the blends is more ordered and tighter after introducing the bio‐additive chlorophyll derivatives to the system compared to the pristine PM6:Y6 blends. Owing to such a fine‐tuned donor‐acceptor microstructure network, the photovoltaic performance of the H 2 Chl bio‐additive‐based OSC achieves a 17.30% PCE and ZnChl‐based device obtains an efficiency of 16.61%, which is much higher than that of the control device with a 15.97% PCE. The result proves the feasibility of introducing environmental‐ and eco‐friendly chlorophyll derivatives as bio‐additives to further improve the photovoltaic performance of the OSCs.